Efeitos do Huanglongbing (HLB) na composição química e características sensoriais de suco de laranja - Bruno Martins Dala Paula (2017)
Huanglongbing (HLB) is the most severe citrus disease in the world. Symptoms of HLB include branches with yellow leaves, premature dropping and changes in fruit sensory quality, loss of leaves and premature death of the tree. The objectives of this work were to evaluate the physicochemical, chemical composition and sensory changes in juice made with HLB symptomatic oranges, as well as to investigate the causes of the bitterness found in HLB orange juice, other than the bitter limonoids, limonin and nomilin. The physicochemical caracteristics and chemical composition were evaluated in juice made with Valencia oranges harvested throughout the season (February, March, April and May 2012). This study confirmed the changes of some chemical composition over the harvest season, with better attributes for processing in the mid-season. Then, a literature review and laboratory analysis evaluating the effects of HLB on physicochemical, chemical composition and sensory characteristics were conducted. Both, review and laboratory analysis, revealed increases of titratable acid (TA), levels of citric acid, limonin and nomilin, among other secondary metabolites, and a decrease of soluble solid contents (SSC), SSC/TA, sugars and malic acid contents. The juice from HLB symptomatic oranges had higher values for the sensory attributes: bitterness, sourness, metallic and umami tastes; flavors of grapefruit, orange peel and staleness; and astringent, burning and tingling month-feels compared to healthy juice. Non-volatile compounds were extracted from Valencia orange juice and fractionated and sensorially described. Bitterness was detected in the fraction containing limonin and nomilin as well as in fractions which did not contain these limonoids, but prevalence of hydroxycinnamic acids. This evidences the existence of other compounds, possibly hydroxycinnamate acids, involved with the typical HLB-bitterness.